Calcinosis cutis universalis in a patient with systemic lupus erythematosus: a case report. (October 2020) - Khudadah, Mohammad; Jawad, Ali; Pyne, Debasish
Calcinosis cutis is a deposition of calcium salts in the skin and subcutaneous tissue which can occur in connective tissue diseases such as scleroderma, dermatomyositis, myositis and overlap syndrome, but rarely in association with systemic lupus erythematosus (SLE). It is subdivided into a localized 'circumscripta' and diffuse 'universalis'. The few reported cases of calcinosis in SLE were mainly of the circumscripta type. Calcinosis universalis is extremely rare and is usually associated with a history of chronic active SLE in female patients, with few proven effective treatments. We report a case of a young female patient with a long and complicated history of SLE. She presented with widespread pain and tenderness associated with multiple subcutaneous skin lesions. She was found to have evidence of calcinosis universalis on X-rays. Investigations did not reveal any associated conditions that could explain this diagnosis other than her prolonged history of SLE.